2017
DOI: 10.1149/2.1041714jes
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Pd/Carbon Vulcan XC-72R Nanoflakes Catalysts for Ethanol Oxidation Reaction in Alkaline Media by RoDSE Method

Abstract: The Rotating Disk Slurry Electrodeposition (RoDSE) technique is a novel method allowing to deposit electrochemically metal nanoparticles on a given conductive support and produce a powder catalyst for diverse applications, for example, ethanol oxidation reaction (EOR). This technique was used to electrodeposit Pd nanoparticles on carbon Vulcan XC-72R nanoflakes at three different applied potentials (0.0, 0.4, and 0.7 V vs. RHE). The potentials were chosen based on different regions of Pd electrodeposition on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…It is found that the existence of either of these features alone is insufficient to yield highly H 2 O 2 -selective electrocatalysts. It has been reported that Pd electrodeposition from solutions with higher Pd precursor concentrations results in crystalline Pd particles, which is consistent with the results here and the observed deleterious effect of crystallinity on H 2 O 2 selectivity.…”
Section: Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is found that the existence of either of these features alone is insufficient to yield highly H 2 O 2 -selective electrocatalysts. It has been reported that Pd electrodeposition from solutions with higher Pd precursor concentrations results in crystalline Pd particles, which is consistent with the results here and the observed deleterious effect of crystallinity on H 2 O 2 selectivity.…”
Section: Results and Discussionsupporting
confidence: 93%
“…Figure f shows CVs recorded in N 2 -saturated pure HClO 4 solution for electrodes deposited in situ in O 2 -saturated PdCl 2 /HClO 4 solutions. The magnitudes of the reversible waves for both reduction and oxidation of Pd increase with increasing concentration of PdCl 2 , indicating deposition of more Pd and larger nanoparticles . Data resulting from the measurement of the electrochemically active surface area (ECSA) of in situ-deposited Pd samples (Table S2) are in agreement with the CV results, and the measured H 2 O 2 current was normalized by ECSA (Figure S17).…”
Section: Results and Discussionsupporting
confidence: 66%
“…The challenge to overcome it is to obtain a bulk production of highly dispersed iron-based QDs onto powdered carbon substrates, especially for in-situ H 2 O 2 generation via ORR. , Equally important, the interface metal–carbon must be controlled to ensure a continuous electron pathway between them. A novel and successful electrochemical method, known as the rotating disk slurry electrodeposition technique (RoDSE), have been applied to deposit metal nanoparticles on different support materials for bulk production of catalyst powder. ,, In RoDSE, a circular flux of solution occur by means of the working electrode rotation. Flux is maintaining constant, replacing continuously the concentration of carbon nanostructures and metallic ions in the diffusion layer, allowing the electrodeposition of the metal to take place at the carbonaceous support .…”
Section: Introductionmentioning
confidence: 99%
“…The inductively coupled plasma optical emission spectrometry (ICP-OES) was carried out using Optima 8000 Perkin Elmer ICP–OES (PerkinElmer, Inc.). Samples were prepared according to the procedure previously reported 51,52 with a minor modification (see Table S1 in SI). The energy dispersive X-ray (EDX) spectra were obtained in a scanning electron microscope (SEM) JEOL JSM-5800LV with operating voltage of 20 kV.…”
Section: Methodsmentioning
confidence: 99%